Evangelism Mission in the Trap of Christianization Issues: An Attempt to Restore an Inclusive Alternative Evangelism Model in Diverse Indonesia - Widjaja, Imron; Simangunsong, Amran (LPPM - Sekolah Tinggi Teologi Indonesia Jakarta, 2025)
The mission of evangelism in Indonesia is often hampered when non-Christians identify it as a Christianization movement. For Muslims in particular, Christianization is considered apostasy. This issue has long been fanned as a trigger for the emergence of radical Islamic movements. Many sources record that Christianization is launched not only to atheists or anists, but also to those who have adopted official religions. Indeed, the pure and sincere mission of evangelism has been tainted with a new form of what non-Christians call Christianization? What is the difference between evangelism and Christianization? Is it true that Christianization has become a coordinated, systemized and massive movement as is widely discussed by many media, or is it just a one-sided accusation? This paper will examine the empirical facts and re-question the truth. The research method used is qualitative descriptive, through library research and in-depth observation of facts in the field. The result of this article is a call for a more inclusive and subtle approach to evangelism in Indonesia, distinguishing it from Christianization, to foster interfaith harmony and avoid colonial perceptions. This article contributes by distinguishing between evangelism and Christianization, highlighting the importance of adopting a subtle, inclusive approach to evangelism in Indonesia to avoid the perception of it as a form of Christianization and to foster interfaith harmony.